2014
DOI: 10.1186/1471-2458-14-542
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of lifestyle and psychosocial problems and persistence of adverse lifestyle over two-year follow-up among Finnish adolescents

Abstract: BackgroundAdolescent’psychosocial problems associate with unhealthy behaviors, but data on co-occurring patterns is sparse. We investigated 1) whether adolescents could be categorized into meaningful subgroups with respect to psychosocial and lifestyle factors, 2) whether the prevalence of physical inactivity, overweight and smoking vary within the subgroups and 3) whether these unhealthy behaviors persist in a two-year follow-up.MethodsThe study was based on a subgroup of the 1986 Northern Finland Birth Cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 69 publications
2
28
1
1
Order By: Relevance
“…We assessed models with cluster numbers of one to seven and determined the best-fitting cluster solution of these candidates by calculating the Akaike information criterion (AIC), the Bayesian information criterion (BIC), the sample-size adjusted BIC (SSABIC), the Lo-Mendell-Rubin's adjusted likelihood ratio test (LRT), average latent class classification accuracy, and entropy measures [13]. The estimation procedure of the number of the latent clusters for both genders has been presented in detail previously [13]. The statistical program M-Plus Version 6.11 was used for the LCA.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We assessed models with cluster numbers of one to seven and determined the best-fitting cluster solution of these candidates by calculating the Akaike information criterion (AIC), the Bayesian information criterion (BIC), the sample-size adjusted BIC (SSABIC), the Lo-Mendell-Rubin's adjusted likelihood ratio test (LRT), average latent class classification accuracy, and entropy measures [13]. The estimation procedure of the number of the latent clusters for both genders has been presented in detail previously [13]. The statistical program M-Plus Version 6.11 was used for the LCA.…”
Section: Methodsmentioning
confidence: 99%
“…We first attempted to consider all variables as continuous in the LCA model, but because of too small group sizes we found that it is necessary to use alternative methods to minimise information loss while best representing the data. The procedure behind the selection of using categorical and continuous variables is explained elsewhere in detail [13].…”
Section: Psychosocial and Lifestyle Variablesmentioning
confidence: 99%
See 3 more Smart Citations